1988
DOI: 10.2307/2403758
|View full text |Cite
|
Sign up to set email alerts
|

Seed Bank Dynamics in Mimosa pigra, an Invasive Tropical Shrub

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Applied Ecology. SUMMARY(1) The dynamics of the seed bank of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…Thus, a complete eradication of lantana requires repeated uprooting of successive crops for several consecutive years (Tireman 1916). Other invasive species (e.g., Mimosa pigra in Australia; Lonsdale et al 1988) have been known to enrich the soil with their own seeds (up to 12,000 seeds/ m 2 , a number that is several times greater than seed densities recorded under other tropical secondary vegetation); lantana may be an example of a similar successful coloniser.…”
Section: Figurementioning
confidence: 99%
“…Thus, a complete eradication of lantana requires repeated uprooting of successive crops for several consecutive years (Tireman 1916). Other invasive species (e.g., Mimosa pigra in Australia; Lonsdale et al 1988) have been known to enrich the soil with their own seeds (up to 12,000 seeds/ m 2 , a number that is several times greater than seed densities recorded under other tropical secondary vegetation); lantana may be an example of a similar successful coloniser.…”
Section: Figurementioning
confidence: 99%
“…Changes to the seed bank (Lonsdale et al 1988, Holmes & Cowling 1997, Drake 1998 2000). In freshwater systems, population size, recruitment, and growth of native freshwater mussels all stabilized or increased a decade after the zebra mussel invasion, but these measures have not rebounded to pre-invasion levels, and the body condition measure of native mussels remains low (Strayer & Malcom 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lonsdale et al (1988) stated that persistence of seeds in soil seed banks is a critical component for maintaining populations of weedy species. Grant-Lipp (1966) indicated that rush skeletonweed seeds may acquire a secondary dormancy when exposed to high temperatures.…”
Section: Discussionmentioning
confidence: 99%